Investigation of Magnetic Anisotropy and Barkhausen Noise Asymmetry Resulting from Uniaxial Plastic Deformation of Steel S235 - Martin Pitoňák; Miroslav Neslušan; Peter Minárik; Jiří Čapek; Katarína Zgútová; Martin Jurkovič; Tomáš Kalina (Applied Sciences, 2021)
This study investigates alterations in magnetic anisotropy and the marked asymmetry in Barkhausen noise (MBN) signals after the uniaxial plastic straining of steel S235 obtained from a shipyard and used as standard structural steel in shipbuilding. It was found that the initial easy axis of magnetisation in the direction of previous rolling, and also in the direction of loading, becomes the hard axis of magnetisation as soon as the plastic strain attains the critical threshold. This behaviour is due to the preferential matrix orientation and the corresponding realignment of the magneto-crystalline anisotropy. Apart from the angular dependence of MBN, the asymmetry in the consecutive MBN bursts at the lower plastic strains is also analysed and explained as a result of magnetic coupling between the grains plastically strained and those unaffected by the tensile test. It was found that, by increasing the degree of plastic strain, the marked asymmetry in MBN tends to vanish. Moreover, the asymmetry in MBN bursts occurs in the direction of uniaxial tension and disappears in the perpendicular direction. Besides the MBN technique, XRD and EBSD techniques were also employed in order to provide a deeper insight into the investigated aspects.